Real Distance Measurement Using Object Detection of Artificial Intelligence (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Artificial intelligence technology is developing rapidly in recent years. The purpose of this paper is to measure the distance to an object using this. In order to measure the distance, two separate pictures from same angles of the object will be taken. It extracts sizes for the same object in two pictures. In order to do this in real time, object detection technology of Artificial Intelligence on mobile phone was used.  In this paper, a method for measuring the distance from two pictures is presented. The proposed method was implemented as a prototype on iOS. In order to measure the performance of distance measurement, experiments were conducted in various environments. In the experiments, the empirical data yielded some discrepancies with the actual measurement. This was a result of errors occurring in the object detection process where the actual size of the object was calculated. Despite these discrepancies, this method of object detection may be widely used in instances where accurate measurements are not necessarily required such as guidance systems for the visually impaired.